2011
DOI: 10.1634/theoncologist.2011-0151
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report: Vitamin D Deficiency in Advanced Cancer Patients with Symptoms of Fatigue or Anorexia

Abstract: Background. Vitamin D deficiency in noncancer patients is associated with symptoms of fatigue, muscle weakness, and depression. These symptoms are common among advanced cancer patients. We investigated the prevalence of low serum vitamin D levels in cancer patients with fatigue or poor appetite and their association with symptom burden and other correctable endocrine abnormalities.Methods. This was a retrospective review of 100 consecutive cancer patients with appetite or fatigue scores of >4 of 10 referred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 35 publications
1
47
1
8
Order By: Relevance
“…In addition, we have previously reported that in 61 male patients with advanced cancer who had been tested for 25 hydroxy vitamin D and BT, there was a trend toward a positive association between vitamin D and testosterone. 19 In the current study with a larger sample size, no significant association among TT, FT, or BT with vitamin D was noted.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, we have previously reported that in 61 male patients with advanced cancer who had been tested for 25 hydroxy vitamin D and BT, there was a trend toward a positive association between vitamin D and testosterone. 19 In the current study with a larger sample size, no significant association among TT, FT, or BT with vitamin D was noted.…”
Section: Discussioncontrasting
confidence: 56%
“…[678] There are many reports which indicate high prevalence of low vitamin D in the general population. [910] Low vitamin D leads to bone abnormalities (e.g., osteomalacia, osteopenia, and osteoporosis) and worsens muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is not only crucial for proper formation and mineral homeostasis of bones [15], but it is also vital for the proper immune and nervous systems function [16,17]. It was demonstrated that cancer patients more often suffer from vitamin D deficiency (< 50 nmol/L) [18]. Moreover, cancer patients with a lower vitamin D level experienced more intense pain and in consequence, needed higher opioids doses [19].…”
Section: Vitamin Dmentioning
confidence: 99%